2011
DOI: 10.22358/jafs/66195/2011
|View full text |Cite
|
Sign up to set email alerts
|

The dose response effects of liquid and lyophilized <i>Carnobacterium divergens</i> AS7 bacteriocin on the nutrient retention and performance of broiler chickens

Abstract: Efficacy of bacteriocin-divercin AS7 supplementation of broiler diets was evaluated. In two experiments one-day-old Ross 308 males were allocated randomly to six and eight dietary treatments, respectively, with 10 replicates (10 birds per replicate). In both experiments the birds were fed on diet non supplemented (negative control, NC) and supplemented with salinomycin (positive control, C). In Experiment 1, the effects of supplementation of the NC diet with 100, 200 or 800 units of liquid divercin, and in Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This is in agreement with Kierończyk et al [16], where the positive effect of nisin on the BWG, FI, and FCR was noticed only in the first period. In contrast to the above, divercin AS7 characterized by even low activity, i.e., 100 AU, 200 AU, and 300 AU, positively affected the FCR value of broiler chickens [57]. Additionally, divercin AS7 exerted a similar effect on the BWG and FCR as salinomycin [58].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with Kierończyk et al [16], where the positive effect of nisin on the BWG, FI, and FCR was noticed only in the first period. In contrast to the above, divercin AS7 characterized by even low activity, i.e., 100 AU, 200 AU, and 300 AU, positively affected the FCR value of broiler chickens [57]. Additionally, divercin AS7 exerted a similar effect on the BWG and FCR as salinomycin [58].…”
Section: Discussionmentioning
confidence: 82%
“…In terms of broiler chickens, only two bacteriocins, i.e., divercin AS7 and nisin, have been partially examined in terms of their dosage [23,57]. Hitherto, it was mentioned that nisin at high activity (900 IU and 2700 IU) has shown the most efficient performance in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…All details regarding preparation and concentration analyses of nisin have been reported previously by . In the first experiment only, nisin was encapsulated in a fat matrix as described in detail by Józefiak et al (2011). The second experiment was carried out without nisin encapsulation, as preliminary data showed that encapsulated nisin does not differ from nonencapsulated nisin in the case of broiler growth performance (unpublished data).…”
Section: Preparation Of Nisin and Analysis Of Nisin Concentrationmentioning
confidence: 99%
“…For its ability to produce bacteriocins, this species has been used in food with the aim to reduce spoilage and pathogenic bacteria (Richard et al., ; Leisner et al., ; Rihakova et al., ). C. divergens has been also studied as probiotic for fish, such as Atlantic cod ( Gadus morhua L.) (Lauzon et al., ), Atlantic salmon ( Salmo salar L.) (Ringø et al., ) and rainbow trout ( Oncorhynchus mykiss ) (Kim and Austin, ), and as probiotic for chicken for fattening (Jözefiak et al., ).…”
Section: Assessmentmentioning
confidence: 99%